Responding to Domestic and Family Violence: A Qualitative Study on the Changing Perceptions of Frontline Police Officers - Maple, Emily (Violence against women, 2021)
Police officers gave accounts of how their perceptions toward Domestic and Family Violence have changed over repeated exposure to these types of incidents as first responders. Interviews were conducted with 16 police officers in an Australian state. Officers expressed a desire to help people and reported personal growth through increased interpersonal skills and open-mindedness but many also became disillusioned. Officers highlighted futility, paperwork, and scrutiny of their actions as factors that inhibited their ability to cope. The findings imply that although officers’ competence may increase, their well-being and capacity to do their job effectively and compassionately may become impaired.